Review: Quantitative Extraction and Analysis of Grape and Wine Proanthocyanidin and Stilbenes - Sun,Baoshan (2005)
From the point of view of biological importance, proanthocyanidins (condensed tannins) and stilbenes (1,2-diarylethenes) are the two most important classes of polyphenols in grape and wine, which have attracted considerable attention of the international scientific community during the last fifteen years, due essentially to their potential beneficial health effects, related to their protective action towards cardiovascular disease and the oxygen free radical scavenger capacity. Numerous research works on proanthocyanidins and stilbenes have been published, but the majority of them have focused on the structural identification and biological activities of these compounds. Furthermore, less attention has been paid on their quantitative aspects and few analytical methods have been validated. This paper introduces briefly grape and wine proanthocyanidins and stilbenes and presents some works realized in our laboratory concerning quantitative extraction and analysis of these compounds.